Consumer Price Index Manual : Theory and Practice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The consumer price index (CPI) measures the rates at which the prices of consumer goods and services are changing over time. It is a key statistic for purposes of economic and social policymaking, especially monetary policy and social policy, and has substantial and wide-ranging implications for governments, businesses, and workers, as well as households. This important and comprehensive manual provides guidelines for statistical offices and other agencies responsible for constructing CPIs and explains in depth the methods that are used to calculate a CPI. It also examines the underlying economic and statistical concepts and priniciples needed for making choices in efficient and cost-effective ways and for appreciating the full implications of those choices. The following international organizations, concerned both with the measurement of inflation and with policies designed to control it, have collaborated on the preparation of this manual: the International Labour Office; the International Monetary Fund; the Organization for Econmomic Co-operation and Development; the Statistical Office of the European Communities (Eurostat); the United Nations Economic Commission for Europe; and the World Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet